Exons 19 and 21 of Epidermal Growth Factor Receptor Are Highly Conserved in Squamous Cell Cancer of the Head and Neck. (1st December 2009) - Carlson, Matthew; Wuertz, Beverly; Lin, Jizhen; Taylor, Randy; Ondrey, Frank
Abstract : Objective . Epidermal growth factor receptor (EGFR) tyrosine kinase inhibition (TKI) is a promising treatment in upper aerodigestive malignancies. EGFR inhibitors might be more effective in patients whose tumors harbor specific EGFR mutations. The presence of specific EFGR mutations is predictive of over a 75% response rate to TKI therapies as compared to 10% in wild type cases of non-small cell lung cancer. Our objective was to examine whether these mutations might occur in upper aerodigestive cancers. Design . DNA was extracted from 20 head and neck squamous cell tumors and 4 squamous cell carcinoma cell lines and sequenced the receptor using published primer pairs. We then compared the results against published mutations. Results . No exon 19 or 21 mutations were found in any of the 20 tumors and 0 of 4 cell lines. Based on the tumor data we would predict that no greater than 8% of head and neck tumors (CI 97.5%) would be likely to harbor either of these mutations. Conclusions . Our findings are comparable to results recently published of Korean, Austrian, and Spanish patient populations and we conclude that exon 19 and 21 EGFR mutations are not more common in head and neck cancer than in nonsmall-cell carcinoma.